Application of LQG and H∞ gain scheduling techniques to active suppression of flutter - Rosique, Miguel Á.; Alamin, Raheeg; Whidborne, James F. (Elsevier, 2019)
Aircraft flutter behaviour is highly dependent on flight conditions, such as airspeed, altitude and Mach number. Thus when closed-loop control is applied to suppress flutter, if these variations are taken into account then improved performance can be obtained if the controller has a certain degree of adaptivity to the variations. In this paper, a Linear Parameter-Varying (LPV) model of a rectangular wing including a trailing-edge control surface is considered. Two different gain scheduling controllers based on LQG and H∞ techniques are designed to suppress flutter and reject perturbations. Simulations of the closed-loop system show that gain scheduling techniques are capable of fully stabilizing the system over the full range of the considered air velocity, and they increase flutter speed by more than 90%.
Keywords: Flexible structure control; Flutter; Aeroservoelasticity; LPV; Gain scheduling; H∞; LQG